2018
DOI: 10.1089/rej.2018.2056
|View full text |Cite
|
Sign up to set email alerts
|

ATP Synthase, a Target for Dementia and Aging?

Abstract: Advancing age is the biggest risk factor for development for the major life-threatening diseases in industrialized nations accounting for >90% of deaths. Alzheimer's dementia (AD) is among the most devastating. Currently approved therapies fail to slow progression of the disease, providing only modest improvements in memory. Recently reported work describes mechanistic studies of J147, a promising therapeutic molecule previously shown to rescue the severe cognitive deficits exhibited by aged, transgenic AD mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Consequently, J147 can cause an increase in intracellular calcium leading to activation of the AMPK/mTOR pathway, a canonical longevity mechanism [35]. Activation by phosphorylation of AMPK subsequently leads to reduction of unnecessary ATP expenditure by decreasing rpS6 kinase activity through less phosphorylation [35,[39][40][41]. Surprisingly, our data indicated, if anything, a further decline of the surgery-induced lower phosphorylated AMPK to total AMPK and phosphorylated rpS6 and total S6, indicating no difference in activation of AMPK or rpS6.…”
Section: Mechanisms (Neuro)inflammation and Neurogenesismentioning
confidence: 51%
See 2 more Smart Citations
“…Consequently, J147 can cause an increase in intracellular calcium leading to activation of the AMPK/mTOR pathway, a canonical longevity mechanism [35]. Activation by phosphorylation of AMPK subsequently leads to reduction of unnecessary ATP expenditure by decreasing rpS6 kinase activity through less phosphorylation [35,[39][40][41]. Surprisingly, our data indicated, if anything, a further decline of the surgery-induced lower phosphorylated AMPK to total AMPK and phosphorylated rpS6 and total S6, indicating no difference in activation of AMPK or rpS6.…”
Section: Mechanisms (Neuro)inflammation and Neurogenesismentioning
confidence: 51%
“…AMPK and rpS6: Previous research showed that J147 can bind to and partially inhibit the mitochondrial alfa-F1 subunit of ATP synthase (ATP5A) and therefore promote cell survival and reduce specific changes associated with age [35,[39][40][41]. To explore whether inhibition of ATP synthase (ATP5A) may play a role in the results of the present study, AMP-activated protein kinase (AMPK) and ribosomal protein S6 (rpS6) were measured in the hippocampus [35].…”
Section: Western Blot Hippocampal Tissuementioning
confidence: 92%
See 1 more Smart Citation
“…53 Despite some aspects that remain to be fully understood, this recent model, sustained by Δψ measurements, provides new insights into the BDQ bactericidal mechanism. Even if, unfortunately, BDQresistant strains are increasing, 19 and BDQ cardiovascular side effects of this drug are still a matter of concern, 54 the assessment of BDQ properties opens the path to the design of new antimycobacterial drugs targeting the F 1 F O -ATP synthase. Accordingly, novel compounds named 5228485 and 5220832 selectively targeting the F 1 F O -ATP synthase of M. tuberculosis and showing excellent bactericidal activity in vitro have been identified.…”
Section: Drugs Targeting F Omentioning
confidence: 99%
“…2) and causes a modest enzyme inhibition that drives intracellular Ca 2+ to activate AMPactivated protein kinase to inhibit mammalian rapamycin target, a known mechanism that extends the life span from worms to mammals. 19 Developing treatments for amyotrophic lateral sclerosis aim at maintaining the mitochondrial function 83 and often reveal a close parallelism between mPTP formation and the activity of the F 1 F O -ATP synthase. The increase in ion conductance due to the mPTP formation and recorded within the c-subunit of the F 1 F O -ATP synthase 12 is inhibited by the neuroprotective drug dexpramipexole, which induces conformational changes in the F 1 F O complex.…”
Section: F 1 F O -Atp Synthase Aging and Neurodegenerative Disordersmentioning
confidence: 99%